2018
DOI: 10.1177/0961203318811603
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset biopsy-proven lupus nephritis without other associated autoimmune diseases: severity and long-term outcome

Abstract: Background/Purpose Lupus nephritis (LN) usually develops within the first years of systemic lupus erythematosus (SLE) onset and rarely after that. There are scarce studies comparing early- versus late-onset nephritis (before versus after five years of SLE diagnosis). The aim of this study was to compare the severity and long-term outcome (after 7 years) in these two, late-onset and early-onset, nephritis groups. Methods This study included 93 patients from rheumatology tertiary centers from Brazil and Italy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…The studies' conclusions varied and are controversial; Varela et al compared early-onset and late-onset LN and reported no signi cant difference in nephritis development or histological type [10], and Ugolini-Lopes et al observed no differences in serum Cr levels or the prevalence of ESKD or mortality after 7 years of follow-up [11]. A recent investigation comparing the disease pro les and outcomes of early-onset and late-onset LN patients did not reveal any signi cant differences [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies' conclusions varied and are controversial; Varela et al compared early-onset and late-onset LN and reported no signi cant difference in nephritis development or histological type [10], and Ugolini-Lopes et al observed no differences in serum Cr levels or the prevalence of ESKD or mortality after 7 years of follow-up [11]. A recent investigation comparing the disease pro les and outcomes of early-onset and late-onset LN patients did not reveal any signi cant differences [17].…”
Section: Discussionmentioning
confidence: 99%
“…5%-15% of LN cases developing later [2,26,27]. There are no standardized de nitions of early-onset and late-onset LN, but several studies made clinical comparisons separated by 5 years [10,11,17], and we followed that approach in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It usually occurs within the first years after diagnosis [10] although some patients do develop this complication later on. Few studies [11,12] address to the characteristics of patients with late onset of nephritis that could allow an early identification and treatment.…”
Section: Introductionmentioning
confidence: 99%